Experimental study of thermal damage under compression and tension of Makrana marble - Gautam P.K.; Jha M.K.; Verma A.K.; Singh T.N. (My University, 2025)
This paper studies the physical and mechanical behaviors of a thermally induced damaged marble. Specimens are heated from the temperature of 25–700 °C at the rate of 5 °C min−1 and then cooled down at the rate 0.364 °C min−1 for each testing. For this purpose, various thermophysical properties such as DTA/TGA, X-ray diffraction, primary-wave velocity, and scanning electron microscopy were investigated to assess the crystalline quality, internal core structure, and the microstructure characteristics, respectively. It has been found that, when the specimens are exposed to high temperatures, their color changes significantly and many microcracks are generated in the marble samples. With the increase in temperature, the nonlinearity in the initial deformation stage is enhanced and the stress–strain behavior under compression and tension changes from brittle to ductile. The results show that the changes in compressive and tensile strength can be divided into three temperature zones: 25–200 °C, 200–500 °C, and 500–700 °C. It has been observed that compressive and tensile strength decreases from 57.56 to 70.01% when temperature changes from 25 to 700 °C. It has also been observed that the thermal stress causes the most conspicuous effect and leads to the decomposition of dolomites intocalcium and magnesium oxides. The extensive experimental study of Makrana marble indicates that the elevated temperature condition causes severe thermal damage and forced the considerable change in the microstructure. The detailed analysis of the obtained results shows that the damage threshold temperature of Makrana marble samples is 500 °C. © 2019, Akadémiai Kiadó, Budapest, Hungary.